Transient Analysis and Safety Assessment of Turbofan Engine Structures during Bird Ingestion - Gang Luo; Chi Ma; Wei Chen; Lulu Liu; Zhenhua Zhao (International Journal of Aerospace Engineering)
The high bypass ratio turbofan engine’s load-carrying structure transient response during bird ingestion was analyzed in accordance with the engine bird ingestion certification regulations, the principles of structural safety assessment were represented, and the structural safety analysis and assessment method of Turbo-Fan engine during bird ingestion were proposed. A high bypass ratio turbofan engine’s FEM was established and verified the rationality when its’ operation. Large bird ingestion into an engine’s procedure was conducted, the dynamic responses of key components on engine’s load-carrying structures during the bird ingestion were discussed, and the safety assessment consequence was obtained. We draw a conclusion that the relevant analysis/simulation data could be submitted to engine certification administration as key documents, the structural safety analysis and assessment method of turbofan engine due to bird ingestion could be applied as analysis and prediction work in the engine bird ingestion certification.